Anomalous NIR Luminescence in Mn2+‐Doped Fluoride Perovskite Nanocrystals. Issue 7 (24th March 2014) - Song, Enhai; Ding, Sha; Wu, Ming; Ye, Shi; Xiao, Fen; Zhou, Shifeng; Zhang, Qinyuan
<x xml:space="preserve">Abstract</x> An anomalous near‐infrared (NIR) upconversion (UC) emission band at approximately 770 nm is demonstrated in KZnF3:Yb3+, Mn2+ nanocrystals with heavy Mn2+ doping. This band would enable advanced biological imaging with improved resolution and enhanced penetration depth. Careful studies based on structure analysis, excitation and emission spectra, and luminescence decay curves indicate that this unusual NIR emission (770 nm) originates from the 6A1g(S)4T1g(G)→6A1g(S)6A1g(S) transitions of the Mn2+–Mn2+ dimers. The influence of Mn2+ concentration and temperature on the Stokes and UC luminescence properties are also investigated. The proposed mechanism for the observed NIR UC emission involves ground state absorption and excited state absorption processes. The present results not only provide a useful and effective approach to achieving pure NIR UC emission, and also new insights into the development of advanced photonic devices and technologies.